THE INFLUENCE OF THE TECHNOLOGY ACCEPTANCE MODEL (TAM) THEORY ON SPONTANEOUS PURCHASING DECISIONS ON SHOPEE PAYLATER USERS INUMENEP DISTRICT - Karomi, Shelma; Purwanto, Edy (Journal MISSY (Management and Business Strategy), 2024)
This study aims to investigate the effect of the Theory of Technology Acceptance Model (TAM) on spontaneous purchasing decisions, with a focus on Shopee Paylater users in Sumenep Regency. TAM is used as a theoretical framework to analyse three main variables: Perceived Ease of Use, Perceived Usefulness, and Attitude Toward Using, on users' impulse buying behaviour. The research method used was a survey using a questionnaire distributed to Shopee Paylater users in Sumenep Regency. Data analysis was carried out using multiple linear regression techniques. The results showed that Perceived Ease of Use and Attitude Toward Using had a significant influence on spontaneous purchasing decisions, while Perceived Usefulness had no significant effect. This finding indicates that users are likely to make spontaneous purchases if they feel that the Shopee Paylater service is easy to use and if they have a positive attitude towards using the service. Thus, the results of this study provide valuable insights for e-commerce companies such as Shopee in designing marketing and product development strategies that can increase user engagement and strengthen spontaneous purchase decisions. This study also provides a theoretical contribution to the understanding of the factors that influence impulse buying behaviour in the context of using e-commerce technology.